Development and evaluation of extruded protein snacks added - GOMES, Karolynne Sousa; BERWIAN, Gabrielle Fusiger; TIEPO, Caroline Balesiefer Vicenzi; COLLA, Luciane Maria (Food Science and Technology, 2023)
This study aimed to develop an extruded protein snack added to lentil flour (L) and textured soy protein (S) and to evaluate the developed formulations sensorially, physicochemically, and physically. Five formulations were prepared: C (100% flour corn (C)), S40% (60% flour corn and 40% soybean), LS20% (80% flour corn, 15% soybean, and 5% lentil), LS15% (85% corn, 7.5% soybean, and 7.5% lentil), and LS10% (90% corn, 7% soybean, and 3% lentil). The research was approved by the Research Ethics Committee of the Universidade de Passo Fundo (55484622.2.0000.5342). Seventy untrained tasters participated in the acceptance test, where the LS15% and LS10% formulations were the most accepted (83.5 and 80.2%, respectively). In the physicochemical characterization, it was observed that all formulations improve nutritional quality, with a significant increase in protein content (11–23%) in all formulations. Physically, the formulations with corn replacement rates showed higher resistance and lower crunchiness. Furthermore, all formulations showed higher water activity (0.55–0.61 aw) than the standard sample (0.34 aw). Therefore, the incorporation of lentils and soy flours benefited the nutritional quality of the snacks but negatively affected their physical parameters and sensory acceptability.